The Effect of Wife Battery in Lagos State: A Case Study of Amuwo-Odofin LGA of Lagos State - Adedeji, Bethel Oluwatosin; Oyeniyi, Toluwalope Oluwabukola (African Journal of Stability and Development (AJSD), 2018)
Wife battering has become a prevalent phenomenon across the world. Lagos State, Nigeria, is no exception to the menace. The study, which is an explorative study, delves into wife battering, the forms and the prevalence of domestic abuse and its impact on the socio[1]economic well-being of women. The study was conducted in Amuwo-Odofin Local Government Area of Lagos State. Amuwo-Odofin was selected because there is a shelter home for battered women there. Structured and unstructured interview guides were used to solicit for information from victims of spousal battering in Amuwo-Odofin Local Government Area of Lagos and from advocates of gender-based violence. The research proposes the establishment of family counselling centres and the need for the involvement of print and electronic media in educating the ills of wife battering. Religious leaders and community leaders will also need to play more roles in helping to change the attitude of their followers towards spousal violence, and generally violence against women. The study concludes that the Nigerian government should work towards enforcing its legislation at all levels of governance against perpetrators of wife battering). This will help reduce the high incidences of wife battering and its attendant consequences, not only in Amuwo-Odofin but also, across the country